2015
DOI: 10.1080/21645515.2015.1101524
|View full text |Cite
|
Sign up to set email alerts
|

Improving rates of maternal immunization: Challenges and opportunities

Abstract: Objectives: An increasing number of vaccines are recommended or are being developed for use during pregnancy to protect women, fetuses, and/or newborns. For vaccines that are already recommended, vaccine uptake is variable and well below desired target. We reviewed the literature related to factors that affect a healthcare provider's recommendation and a woman's willingness to be vaccinated during pregnancy. Design: A scoping review of published literature from 2005 to 2015 was undertaken and all relevant arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 76 publications
(279 reference statements)
7
65
0
3
Order By: Relevance
“…However, a significant number of women reported they had not been offered information and fears persist about the perceived risk of miscarriage or harm to the baby. Similar concerns have been highlighted in other studies exploring attitudes to maternal immunization, among different populations such as in the USA and Australia . Our data suggest that emphasizing the protection for the baby and the potential severity of the infections, rather than benefit for mother or protection from a common illness, could be more effective at promoting vaccine uptake.…”
Section: Discussionsupporting
confidence: 85%
“…However, a significant number of women reported they had not been offered information and fears persist about the perceived risk of miscarriage or harm to the baby. Similar concerns have been highlighted in other studies exploring attitudes to maternal immunization, among different populations such as in the USA and Australia . Our data suggest that emphasizing the protection for the baby and the potential severity of the infections, rather than benefit for mother or protection from a common illness, could be more effective at promoting vaccine uptake.…”
Section: Discussionsupporting
confidence: 85%
“…Also, 67% of the midwives reported that they would welcome better access to evidence of effectiveness. Similar findings were reported by other studies [110]. Lack of knowledge about disease risks and vaccine safety and efficacy was also frequently cited as barriers by pregnant women, which underscores the need for clearer education in this area [110].…”
Section: Overcoming Barriers To Maternal Immunizationsupporting
confidence: 78%
“…Commencing antenatal care late was associated with lower coverage, and recommendations by health care providers have a strong influence on the likelihood of vaccination during pregnancy. 23 Further, we found that GP-led care was associated with higher rates of vaccination than obstetrician-led care, possibly reflecting the expertise of GPs in delivering a range of vaccines. It may also indicate attitudinal, logistic or other barriers to obstetricians offering vaccines, such as the lack of systems and processes for their ordering or storing vaccines.…”
Section: Discussionmentioning
confidence: 69%
“…Our results suggest several steps for improving vaccination coverage among pregnant women (Box 6). Commencing antenatal care late was associated with lower coverage, and recommendations by health care providers have a strong influence on the likelihood of vaccination during pregnancy . Further, we found that GP‐led care was associated with higher rates of vaccination than obstetrician‐led care, possibly reflecting the expertise of GPs in delivering a range of vaccines.…”
Section: Discussionmentioning
confidence: 99%